Analisis Ketahanan Pangan Rumah Tangga pada Program Pekarangan Pangan Lestari - Senjawati, Nanik Dara; Azizah, Alifah Firda (Jurnal Sosial Ekonomi Pertanian, 2024)
The research was aimed to analyze the level household food security in Mrican. This research is quantitative research using the case study method which is the only suistanable food yard program recipients (P2L) in Caturtunggal, Depok, Sleman. The sampling method used disproportionate stratified random sampling with a total sample 44 consisting of 22 household receiving P2L and 22 household not receiving P2L (Non-P2L). The data analysis technique used the analysis of the level of food security. The result showed that the level of household condition that experience food security in Mrican was in a food insecure condition of 75%. However, there are household conditions that experience food insecurity by 4,55% and food security 20,45%.